Potentiometric Investigations on Cation-Selective Electrodes based on Macrocyclic and Acyclic Amides as Ionophores - Gupta, Nidhi Rani (My University, 2009)
This Thesis describes fabrication of liquid membrane based ion selective electrodes for biological active metal ions like Ag+, Zn2+, Cu2+, Ni2+ and Co2+ ions using amide, amine, and imine macrocycles containing heteroatoms. The proposed electrodes exhibit good Nernstian response in terms of wide measuring range, detection limit and life time. All the electrodes show good selectivity behavior for target metal ion over a large number of alkali, alkaline earth and transition metal ions. They were also successfully applied in the non aqueous medium up to an appreciable extent and in the real life samples for the determination of respective metal ions.
Ph.D. Thesis
Keywords: Ion selective electrode; potentiometry